Impact of School Nurse Asthma Education Programme on School Nurses' Asthma Knowledge and Self-Efficacy Levels: A Quasi-Experimental Study - Al Kindi, Zainab Khalifa (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2023)
Background Asthma is a prevalent chronic disease that affects millions of individuals worldwide, with an increasing prevalence among children. In Oman, asthma is a significant health problem, with a prevalence of 11.5% among school-age children. School nurses play a critical role in the management of asthma in schools, including the assessment of symptoms, administration of medication, and education of students, teachers, and parents about asthma management. However, research suggests that school nurses may have insufficient knowledge and skills related to asthma management, and there is a need to develop educational programmes to address this issue. Aim To investigate the impact of School Nurse Asthma Education Programme (SNAEP) on school nurses' knowledge and self-efficacy levels. Methods This study is a two-phase quasi-experimental design. In phase 1, a descriptive needs assessment survey was conducted among school nurses from governmental schools at Muscat Governate to identify asthma educational needs. In phase 2, the educational programme -SNAEP- was delivered face-to-face. The outcomes of knowledge and self-efficacy were assessed at four data collection times: before the programme, immediately after, 3 months and six months after the programme. Results The needs assessment survey revealed that there is a need for a written scope of practice for school nurses to facilitate the provision of asthma care at schools. The study revealed a significant improvement in school nurses' asthma management knowledge (p = 0.00) and self-efficacy levels (p = 0.00) up to six months after the intervention programme. There was a strong positive correlation between knowledge and self-efficacy before the programme (r = 0.90) and a moderate positive correlation immediately post-intervention (r = 0.44). School nurses exhibited lower knowledge and self-efficacy in items related to medication administration and delivery device skills. Conclusion Overall, the study provides valuable insights into asthma educational needs of school nurses and interventions required to improve the asthma management knowledge and skills of school nurses in Oman. SNAEP was successful in improving the school nurses' knowledge and self-efficacy levels. Ongoing in-service training and refresher programmes are necessary to promote the retention of knowledge and skills. Interactive teaching methods were found to be effective in promoting knowledge acquisition and retention, particularly in teaching medication indications
APPROVED
Keywords: Asthma, Schools, School Nurse, Education, Asthma Education